2016
DOI: 10.3233/jad-160036
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Elongation Factor 1A Expression is Correlated with Synaptic Plasticity Impairments in Alzheimer’s Disease

Abstract: Synaptic dysfunction may represent an early and crucial pathophysiology in Alzheimer’s disease (AD). Recent studies implicate a connection between synaptic plasticity deficits and compromised capacity of de novo protein synthesis in AD. The mRNA translational factor eukaryotic elongation factor 1A (eEF1A) is critically involved in several forms of long-lasting synaptic plasticity. By examining postmortem human brain samples, a transgenic mouse model, and application of synthetic human Aβ42 on mouse hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Suppression of eIF2α phosphorylation corrected AD-associated cognitive and synaptic plasticity defects (17), indicating a crucial role of translation initiation dysregulation in AD pathogenesis. Mounting evidence suggests an important role for elongation regulation in cognition, with recent studies linking dysregulation of elongation factors with AD pathophysiology (15,(44)(45)(46)(47). Of note, a recent study showed a connection between eIF2 signaling and eEF2 phosphorylation in neurons (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suppression of eIF2α phosphorylation corrected AD-associated cognitive and synaptic plasticity defects (17), indicating a crucial role of translation initiation dysregulation in AD pathogenesis. Mounting evidence suggests an important role for elongation regulation in cognition, with recent studies linking dysregulation of elongation factors with AD pathophysiology (15,(44)(45)(46)(47). Of note, a recent study showed a connection between eIF2 signaling and eEF2 phosphorylation in neurons (48).…”
Section: Discussionmentioning
confidence: 99%
“…Breeders of Tg19959 AD model mice were a gift from George Western blots for postmortem human tissue. Hippocampal tissue from AD, FTD, and LBD patients and their respective age-matched controls was sonicated as previously described (45). Samples containing equal amounts of protein lysate were loaded on 4%-12% Trisglycine SDS-PAGE gels (Bio-Rad, catalog 4561023) for standard gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have observed decreased expression of eEF1A and eEF2 in the brains of PD and AD patients, as well as in mouse models of these diseases; however, the role of elongation in the pathogenesis of these disorders remains unclear (Beckelman et al, 2016a, 2016b, Garcia-Esparcia et al, 2015, 2017; Hernández-Ortega et al, 2016; Li et al, 2005). A better understanding of the importance of these factors in disease is gained when we turn to genetic models and patients with mutations in these genes themselves.…”
Section: Elongation Factors and Impaired Translational Fidelity In Nementioning
confidence: 99%
“…Some of these loci and genes in related pathways have been previously implicated in responses to cellular stress, neurodegeneration, and TBI. [35][36][37][38] Of note, ubiquitin proteins have been implicated in TBI and neurodegenerative disease, and the ubiquitin C-terminal hydrolase-L1 (UCH-L1) has been FDA approved as a robust blood-based biomarker for acute mild brain injury. 39 Blast associated physiological and psychological symptoms linked to DNA methylation and transcriptional changes.…”
Section: Dna Methylation and Transcriptional Changes Associated With Acmentioning
confidence: 99%